Survival from paraquat induced renal impairment in a 17 years old male - Kuotsu, Medo M.; Singh, N. Biplab; Konyak, Nyamnyei; Khruomo, Vikie-o; Kath, Senjele; Dhakal, Deepak; Namanandi, Ashwini (International Journal of Advances in Medicine, 2021)
N, N’-dimethyl-4, 4’-bipyridinium dichloride (paraquat) is a herbicide commonly used in India that leads to fatal outcome on ingestion. Paraquat interferes in the intracellular electron transfer systems inhibiting the reduction of NADP to NADPH resulting in accumulation of superoxide radical causing lipid cell membranes destruction leading to various organ damage. Life threatening effects such as acute kidney injury as paraquat elimination is mainly by kidney, acute respiratory distress syndrome and multi-organ failure are the causes of mortality in paraquat poisoning. There is no specific antidotes for paraquat poisoning so prevention and aggressive decontamination remains the mainstay of management in case of exposure or ingestion. Paraquat poisoning presentation may vary in cases depending on the amount of paraquat consumed and thus the outcome. Here we report a case of a 17 years old male who presented with acute kidney injury following ingestion of paraquat in a suicidal attempt. In our case, induced vomiting of the stomach content readily after ingestion of the poison, early haemodialysis, use of immunosuppression such as methylprednisolone, cyclophosphamide and antioxidants such as acetylcysteine, Vitamin C and Vitamin E as free radical scavenging agent , supportive measures such as adequate hydration and antibiotics might have helped in the patient’s survival. The case fatality remains very high in paraquat poisoning till date owing to lack of effective treatment options.